MXene Quantum Dot/Polymer Hybrid Structures with Tunable Electrical Conductance and Resistive Switching for Nonvolatile Memory Devices. (12th November 2019) - Mao, Huiwu; Gu, Chen; Yan, Shiqi; Xin, Qian; Cheng, Shuai; Tan, Peng; Wang, Xiangjing; Xiu, Fei; Liu, Xiaoqin; Liu, Juqing; Huang, Wei; Sun, Linbing
Abstract: Low‐dimensional MXene materials including MXene quantum dots (MQDs) and nanosheets have attracted extensive attention owing to their unique structures and novel properties, but their most attractive features are still less explored than expected. A systematic study of the memory effects of MQD‐based electronics is reported. Monodisperse MQDs are prepared by using a one‐step facile hydrothermal synthetic method. By varying the MQD content in polyvinylpyrrolidone (PVP) hybrid composite films, the electrical conductance of an indium tin oxide (ITO)/MQD‐PVP/gold (Au) sandwich structure can be tuned precisely from insulator behavior to irreversible resistive switching, reversible resistive switching, and conductor behavior. These irreversible and reversible resistive switches are capable of exhibiting write‐once‐read‐many times (WORM) and flash memory effects, respectively. Both types of devices operate stably under retention testing, with a high on/off current ratio up to 100. The tunable memory and transient features of these hybrid films are likely due to MQD charge trapping due to their quantum confinement and dissolvability of memristive components. The results suggest that MXene nanomaterials are promising as resistive switching trigger for emerging nonvolatile memories for data storage, specially data storage security. Abstract : By varying MQD content in polyvinylpyrrolidone (PVP) hybrid composite films, the electrical conductance of an indium tin oxide (ITO)/MQDs‐PVP/gold (Au) sandwich structure can be tuned precisely from insulator behavior to irreversible resistive switching, reversible resistive switching, and conductor behavior. This allows for write‐once‐read‐many times (WORM) and flash memory effects, both of which are stable under retention testing, with a high ON/OFF current ratio.